37. Two distinct phenotypes of corticomotor hand representation in human motor cortex - Dubbioso, R.; Raffin, E.; Nielsen, S.H.; Madsen, K.H.; Sørensen, P.J.; Nilsson, S.J.; Thielscher, A.; Siebner, H.R. (Clinical neurophysiology, 2017)
Transcranial magnetic stimulation (TMS) can be used to map the corticomotor representations of hand muscles in the precentral motor-cortex (PMC). The spatial peak of the corticomotor representations is often not located in the primary motor cortex (M1HAND), but shows an anterior shift towards the dorsal premotor cortex (PMd) 1. Here we used magnetic resonance imaging (MRI) to test the hypothesis that the PMC shows different structural and functional properties in individuals with a clear “premotor” representation compared to individuals with a preponderant “primary-motor” representation of hand muscles. MRI-measurements and neuronavigated-TMS were performed on twenty-four volunteers (mean age: 24.3±0.9 SE, 12 women). Participants underwent structural MRI to evaluate cortical thickness and curvature of the PMC. We also performed fMRI to evaluate precentral functional activation in the hand-knob during a simple motor task. Sulcus-shape based TMS-mapping was used to obtain mediolateral and posterior-anterior corticomotor excitability profiles of the left abductor-digiti-minimi and first-dorsal-interosseus muscles. In 14 out of 24 individuals (58%), TMS mapping disclosed a clear spatial peak in the stimulation lines overlying the PMd, whereas the remaining 10 subjects (42%) showed maximal motor responses more posteriorly along M1HAND. During fMRI, the “premotor” group displayed a stronger task-related activation in the PMd relative to the “primary-motor” group (p=0.002). No difference between two groups was evident for curvature and cortical thickness. The results confirm that many individuals have a more premotor corticomotor representation of small hand muscles when measured with TMS. This premotor is associated with a stronger premotor activation during simple movements. This association supports the notion of two distinct functional phenotypes of corticomotor hand representations in human PMC: a primary motor and a premotor phenotype.